2007
DOI: 10.1016/j.neuroscience.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor neuroprotection of ethanol-induced neuronal death in rat cerebral cortex is age dependent

Abstract: Organotypic cultures of rat cortex were used to test the hypotheses that nerve growth factor (NGF) is neuroprotective for immature cortical neurons and that ethanol abolishes this neuroprotection in a developmental stage-dependent manner. Samples were obtained on gestational day (G) 16 or postnatal day (P) 3 and cultured with ethanol (0 or 400 mg/dl) and NGF (0 or 30 ng/ml) for 72 hours. Dying neurons were identified as exhibiting terminal nick-end labeling, immunoreactivity for activated caspase 3, or condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The binding of NGF to TrkA results in receptor phosphorylation, followed by the activation of signaling pathways that enhance cell survival and neuronal differentiation. In contrast, signaling via p75NTR can activate pathways of cell death[20]. Therefore, the final effect of NGF is a balance between cell survival signal derived from the TrkA family and cell death signal from the p75NTR[21].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of NGF to TrkA results in receptor phosphorylation, followed by the activation of signaling pathways that enhance cell survival and neuronal differentiation. In contrast, signaling via p75NTR can activate pathways of cell death[20]. Therefore, the final effect of NGF is a balance between cell survival signal derived from the TrkA family and cell death signal from the p75NTR[21].…”
Section: Discussionmentioning
confidence: 99%
“…Three-day-old Long-Evans rat pups from dams fed chow and water ad libitum were used for generating organotypic slice cultures (Mooney and Miller, 2003; 2007a). Animals were anesthetized (100 mg/kg ketamine and 10 mg/kg xylazine) and decapitated.…”
Section: Methodsmentioning
confidence: 99%
“…Ethanol may have differential effects on immature neurons; it may act as a stimulant on them, rather than as a generalized CNS depressant (9). Extensive studies have shown that neurons develop resistance to the effects of ethanol as they mature (10, 11). Other reports have shown that administration of doses of ethanol that would cause extensive neuronal loss in neonatal mice are not associated with loss of neurons in the adult brain (12, 13).…”
Section: Introductionmentioning
confidence: 99%